The differences of cultural awareness based on gender, age, race, and region of the students - Yusri, Fadhilla; Afrida, Yeni (Universitas Negeri Padang, 2022)
Objectives: This study was conducted to reveal differences in cultural awareness based on gender, age, ethnicity, and region of origin.Methods: The research conducted to reveal differences in student cultural awareness based on gender, age, ethnicity, and region of origin is a comparative type. The research sample amounted to 41 people who were selected using the accidental sampling technique. Data was collected by giving the cultural awareness instrument directly to the sample. The research datasets were processed using univariate and multivariate analysis.Results: The results showed that the average cultural awareness score of students was 71.8%, with SD 1.04 being in the medium category. There is no significant difference in student cultural awareness based on gender, age, ethnicity, and region of origin. Differences in gender, age, ethnicity, and region of origin have no impact on the cultural awareness they have. External efforts are needed to increase cultural awareness so that cross-cultural counseling activities can be carried out properly and appropriately.Conclusion: The mastery of student cultural awareness has an impact on the cross-cultural counseling activities that will be carried out. The results of this study can be used as a guide for teachers in the guidance and counseling study program to consider the treatment that can be given to increase the cultural awareness of students in implementing cross-cultural counseling.